2003
DOI: 10.1007/s00431-002-1037-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin injection regimens and metabolic control in an international survey of adolescents with type 1 diabetes over 3 years: results from the Hvidore study group

Abstract: in this international study, metabolic control was unsatisfactory in many adolescents with type 1 diabetes irrespective of the insulin regimen. No improvement in metabolic control was observed in this cross-sectional survey, over 3 years in any of the subgroups. Even the group switching from twice to multiple injections did not improve blood glucose control and the increase in body mass index was most pronounced in this group. Conclusive evidence, however, should be based on prospectively planned, randomised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 39 publications
13
112
3
1
Order By: Relevance
“…The metabolic control in 2873 children and adolescents was studied in 1995 and 1998 in 21 centres from Europe, Japan and the United States [19,20]. From the mean glycated haemoglobin value (8.7%) of this large international study it is staggeringly obvious that despite the almost unacceptable psychological, emotional and social price, the level of glycaemic control achievable in children with modern insulin therapy is far from satisfactory.…”
Section: A Paediatric Perspectivementioning
confidence: 99%
“…The metabolic control in 2873 children and adolescents was studied in 1995 and 1998 in 21 centres from Europe, Japan and the United States [19,20]. From the mean glycated haemoglobin value (8.7%) of this large international study it is staggeringly obvious that despite the almost unacceptable psychological, emotional and social price, the level of glycaemic control achievable in children with modern insulin therapy is far from satisfactory.…”
Section: A Paediatric Perspectivementioning
confidence: 99%
“…Previous studies (2,3) have shown that improved glycaemic control, measured as HbA1c, is important in preventing, delaying or slowing the progression of long-term complications. A high proportion of adolescents do not reach treatment targets for glycated haemoglobin, HbA1c (4)(5)(6), and there is evidence that metabolic control deteriorates during adolescence. There is a correlation between metabolic control in late childhood and during adolescence (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The DCCT and EDIC study clearly showed the importance of a strict glycemic control both in adults and in adolescents with type 1 diabetes (1994). The importance of keeping HbA1c within targets has also been highlighted by other studies, but similarly to the DCCT, subsequent studies have confirmed the difficulties encountered when dealing with young people with type 1 diabetes (Holl et al, 2003;Petitti et al, 2009). Tight glycemic control in the DCCT and subsequent studies was associated with a higher risk of complications, such as hypoglycemia and weight gain (1994).…”
Section: Interventionsmentioning
confidence: 75%
“…Poor glycemic control is a common finding among adolescents with type 1 diabetes Holl et al, 2003). In addition, puberty is associated with a decrease in insulin sensitivity, and adolescents with type 1 diabetes are more insulin resistant when compared with healthy controls (Dunger, 1992).…”
Section: Pubertymentioning
confidence: 99%
See 1 more Smart Citation